Effect of Interface Evolution on Thermal Conductivity of Vacuum Hot Pressed SiC/Al Composites1. Issue 7 (2nd January 2015) - Chen, Zhizhong; Tan, Zhanqiu; Ji, Gang; Fan, Genlian; Schryvers, Dominique; Ouyang, Qiubao; Li, Zhiqiang
<x xml:space="preserve">Abstract</x> The SiC/Al composites have been fabricated by a vacuum hot pressing (VHP) process in order to study the effect of interface evolution on the global thermal conductivity (TC). By optimizing the VHP parameters of sintering temperature and time, the three different kinds of SiC/Al interface configurations, that is, non‐bonded, diffusion‐bonded, and reaction‐bonded interfaces, are formed and identified by measurement of relative density, X‐ray diffraction, scanning and (high‐resolution) transmission electron microscopy. The VHPed composite sintered at 655 °C for 60 min is fully dense and presents a tightly‐adhered and clean SiC/Al interface at the nanoscale, the ideal diffusion‐bonded interface being the most favorable for minimizing interfacial thermal resistance, which in turn results in the highest TC of around 270 W/mK.